2005
DOI: 10.1191/0269215505cr831oa
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to actively and purposely make use of plasticity and adaptability in the neurorehabilitation treatment of multiple sclerosis patients? A pilot project

Abstract: Clinical changes seen with neurorehabilitation were not associated with any detectable changes in fMRI observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
0
26
1
1
Order By: Relevance
“…While no studies to our knowledge have examined changes in brain activation in cognition following cognitive rehabilitation in MS, studies have examined changes post-intervention in the motor domain in MS [15,16]. In controls, Poldrack et al [17] showed that practiced mirror reading resulted in decreased activation in occipital, inferior temporal, and superior parietal cortices and increased activation in occipito-parietal and lateral temporal regions on fMRI.…”
Section: Functional Neuroimaging In Msmentioning
confidence: 97%
“…While no studies to our knowledge have examined changes in brain activation in cognition following cognitive rehabilitation in MS, studies have examined changes post-intervention in the motor domain in MS [15,16]. In controls, Poldrack et al [17] showed that practiced mirror reading resulted in decreased activation in occipital, inferior temporal, and superior parietal cortices and increased activation in occipito-parietal and lateral temporal regions on fMRI.…”
Section: Functional Neuroimaging In Msmentioning
confidence: 97%
“…Some studies suggest that some cortical reorganization in patients with MS may occur, but it is unclear whether this plays a role in MS rehabilitation (Rasova et al 2005). The main effect is likely to be a consequence of improved compensation, adaptation and reconditioning (Rocca et al 2002).…”
Section: Future Of Robotics Technology In the Rehabilitation Of Ms Sumentioning
confidence: 98%
“…Six studies investigated whether motor rehabilitation strategies enhance brain plasticity, as evaluated by either task-related fMRI ( n = 2) [ 26 , 27 ], DTI ( n = 3) [ 28 30 ], or both techniques ( n = 1) [ 31 ] (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%